PERAN NYAMA PAT DALAM KEHIDUPAN MANUSIA PERSFEKTIF AGAMA HINDU - Gede Rai Parsua (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The results of this study, Nyama Pat plays a very important role in human life from newborn to human death. According to Lontar Panugrahan Dalem Nyama Pat is contained in the teachings of Kanda Empat. The role of Nyama Pat or often called Kanda Empat is very instrumental in human life starting from home and in human life which reads